International intangible cultural heritage policy in the neighbourhood: an assessment and case study of Indonesia. Issue 3 (2nd September 2018) - Jones, Tod
ABSTRACT: UNESCO's heritage policies are one of the most extensive global drivers of landscape and cultural transformation and investment. In response to complaints about Western and object-focussed bias in World Heritage, a push within UNESCO generated a new convention and a new category of heritage: intangible cultural heritage (ICH). Maligned by academic critics, it has nonetheless been an incredibly widespread program internationally with over 170 states signed up to its convention and subject to its obligations. This article provides an assessment of the geographical reach and impact of UNESCO's ICH program, and, through a case study in Indonesia, analysis of its most successful (according to the Indonesian Directorate of Culture) program for the production of batik cloth. Through the case study, I assess the impact of the ICH policy in Indonesia at different levels and for different groups, the scales it has enabled, and its impact on historical batik landscapes.